Multisorted dualisability: change of base - Davey, B; Gouveia, M; Haviar, M; Priestley, H (2011)
We prove that if a quasivariety A generated by a finite family M of finite algebras has a multisorted duality based on M, then A has a multisorted duality based on any finite family of finite algebras that generates it. © 2011 Springer Basel AG.